Pengaruh Dividend Yield, Arus Kas Operasional, dan Profitabilitas Terhadap Return Saham - Sri Ayuni; Hari Setiono; Nur Ainiyah (Indo Publishing, 2026)
Stock returns are a key way for investors to check how well their investments are doing in the stock market. Consumer goods companies that are listed on the Indonesia Stock Exchange saw changes in their stock prices over the three years from 2022 to 2025, with some going up and others going down. This situation requires looking at the main things that affect how much stock prices go up, like dividends, cash flow from operations, and how profitable a company is. This study uses a numerical method and relies on data collected from financial reports and information from the capital market. The sample was chosen on purpose, including 32 companies and making a total of 128 observations over four years. Data analysis was done using multiple linear regression, and the SPSS software was used to help with this process. The results show a strong connection, showing that dividends and operating cash flow greatly affect stock returns.